2000
DOI: 10.1159/000020993
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Ultrasonography of Uteroplacental Circulation Does Not Evoke Harmful CTG Changes or Perinatal Events

Abstract: Objective: To determine whether an intravascular ultrasound contrast agent used in the examination of uteroplacental circulation in late pregnancy has any effect on fetal cardiotocographic (CTG) parameters or fetal well-being. Methods: The uteroplacental circulation of 69 women with singleton third trimester pregnancies was examined by power Doppler with contrast agent (Levovist®; Schering AG, Berlin, Germany) enhancement. Computed CTG examination using Dawes/Redman criteria was recorded just before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Whether three-dimensional perfusion imaging may significantly improve repeatability of quantitative parametric analysis of placental perfusion in rats remains open to future work; (3) the relationship between enhanced signal intensity and concentration of microbubbles should be determined before experiment to select suitable dosage for intravenous injection; (4) concerns of the use of ultrasound contrast agent during pregnancy. However, there is increasing evidence that CEUS is safe during pregnancy [29], [41], [42]. In addition, microbubbles do not cross the placenta and diagnostic CEUS with microbubbles will not increase the permeability of placenta [25].…”
Section: Discussionmentioning
confidence: 99%
“…Whether three-dimensional perfusion imaging may significantly improve repeatability of quantitative parametric analysis of placental perfusion in rats remains open to future work; (3) the relationship between enhanced signal intensity and concentration of microbubbles should be determined before experiment to select suitable dosage for intravenous injection; (4) concerns of the use of ultrasound contrast agent during pregnancy. However, there is increasing evidence that CEUS is safe during pregnancy [29], [41], [42]. In addition, microbubbles do not cross the placenta and diagnostic CEUS with microbubbles will not increase the permeability of placenta [25].…”
Section: Discussionmentioning
confidence: 99%
“…Computerized CTG has seen increased utility over the past decades as a clinical research tool.It has been employed in studies investigating longitudinal changes of biophysical profiles in fetal growth restriction, 76 the effect of different medical investigations, including the maternal glucose ingestion during the oral glucose tolerance test, 77,78 the safety of contrast-enhanced ultrasound with respect to uteroplacental circulation 79 and fetal magnetic resonance imaging. 80 In addition, it has been used to study the development of delivery planning protocols for fetuses with intrauterine growth restriction 81 and risk prediction of neonatal acidaemia at birth in combination with other investigations, 82 the effects of vibroacoustic stimulation on FHR in term fetuses, 83 prediction of acid-base status in placentalinsufficiency when combined with venous doppler investigation, 84 investigationofthe effect of pharmaceutical agents on FHR profiles, 85,86 the effect of maternal co-morbidities (eg, asthma) on FHR 87 and maternal race and ethnicity in FHR patterns, 88 to name a few.…”
Section: Computerized Ctg In Clinical Practicementioning
confidence: 99%
“…23 Another study using primates reported that administration of Levovist does not affect fetal hemodynamic parameters as measured by Doppler ultrasound and suggested that administration of the microbubble agent does not interfere with placental blood flow. 24 In human, Orden et al 25 reported that contrast agent enhancement in the examination of uteroplacental perfusion does not produce any harmful fetal or placental effects in late pregnancy.…”
Section: Safety Of Contrast Media In Obstetricsmentioning
confidence: 99%